Perilaku Petani terhadap Pelaksanaan Tri Hita Karana dalam Upaya Pelestarian Subak Daerah Pariwisata (Kasus Subak Andong, Kecamatan Ubud, Kabupaten Gianyar) - I GUSTI NGURAH MAHA YASTRAWAN; I KETUT SUAMBA; I MADE SARJANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
Farmers’ Behavior Toward the Implementation of Tri Hita Karana in Preserving Subak in Tourism Regions (The Case of Subak Andong, Ubud District, Gianyar Regency) The rapid globalization and growth of tourism have had an impact on the existence of subaks in Bali. Land use change is one of the challenges to preserve subak as a communal organization of Balinese farmers. This study aims to determine the behavior of farmers towards the implementation of Tri Hita Karana in an effort to preserve subaks in tourism areas, especially Subak Andong, which is located in Ubud District, Gianyar Regency. The scope of this research covers the behavior of Subak Andong members, including knowledge, attitude, and application of Tri Hita Karana in an effort to preserve Subak. This study uses a qualitative descriptive analysis method. Based on the research results, it is known that the behavior of the farmers of Subak Andong is very good. The behavioral scores on all categories, i.e., knowledge (86.3%), attitude (85.9%), application (87.1%), are high. The behavior of Subak Andong farmers towards Tri Hita Karana shows a very good result, so that efforts to preserve Subak Andong can go hand in hand with the development of tourism in the area. It is hoped that the behavior of members in Subak Andong will be maintained.